The relative importance of property-specific factors that influence office occupation decisions in P-grade, A-grade and B-grade office buildings in the decentralized office nodes of Johannesburg, South Africa - Meiring, Estelle (My University, 2016)
Purpose – Within the paradigm of consumer behaviour, the purpose of this study was to determine the relative importance of the various property-specific factors that influence office occupation decisions in the decentralized office nodes of Johannesburg. The aim was to provide more definitive information on office space occupation to real estate marketers, managers, investors and owners. Design/Methodology/Approach – A Malaysian study by Adnan et al. (2012) was replicated in the South African context, utilizing their (adjusted) questionnaire survey. After review, Adnan et al.’s (2012) data analysis methods were altered and, in addition, three key-informant interviews were conducted to discuss the results of the survey and to try and gain further insight into the findings. Findings – The three categories that were considered of highest importance were Cost/Financial Considerations, Services and Management. Factors that scored the highest overall were Security & Access Control, Car Parking Provisioning & Accessibility, Electricity Systems & Provisioning and Rental Rate. The categories On-site Amenities, Space Functionality & Atmosphere and Location were considered of least importance. Research Limitations/Implications – The study was confined to property-specific factors and limited to tenants in P-grade, A-grade and B-grade office buildings in the decentralized office nodes of Johannesburg. It also took place during a specific stage of the South African economic cycle. Further research is required to determine the impact of office grade, firm type, firm size and economic climate on office occupation decisions. Originality/Value – No research on this topic exists within the South Africa context and this study contributes to the limited research, internationally, on real estate within the consumer behaviour paradigm.
The relative importance of property-specific factors that influence office occupation decisions in A-grade office buildings in Johannesburg, South Africa
A research report submitted in partial fulfilment of the requirements for the degree of Master of Science in Property Management and Development to the Faculty of Engineering and the Built Environment, University of the Witwatersrand, Johannesburg, 2016
Keywords: Office buildings--South Africa--Johannesburg; Real estate management--South Africa--Johannesburg; Real property--South Africa